Trichosanthes kirilowii Ethanol Extract and Cucurbitacin D Inhibit Cell Growth and Induce Apoptosis through Inhibition of STAT3 Activity in Breast Cancer Cells. (30th September 2013) - Kim, Soon Re; Seo, Hye Sook; Choi, Han-Seok; Cho, Sung-Gook; Kim, Yong Kuk; Hong, Eun Hee; Shin, Yong Cheol; Ko, Seong-Gyu
Abstract : Trichosanthes kirilowii tuber is a traditional medicine which exhibits various medicinal effects including antidiabetic and anticancer activities in several cancer cells. Recently, it was reported that Cucurbitacin D (CuD) isolated from Trichosanthes kirilowii also induces apoptosis in several cancer cells. Constitutive signal transducer and activator of transcription 3 (STAT3), which is an oncogenic transcription factor, is often observed in many human malignant tumor, including breast cancer. In the present study, we tested whether Trichosanthes kirilowii ethanol extract (TKE) or CuD suppresses cell growth and induces apoptosis through inhibition of STAT3 activity in breast cancer cells. We found that both TKE and CuD suppressed proliferation and induced apoptosis and G2/M cell cycle arrest in MDA-MB-231 breast cancer cells by inhibiting STAT3 phosphorylation. In addition, both TKE and CuD inhibited nuclear translocation and transcriptional activity of STAT3. Taken together, our results indicate that TKE and its derived compound, CuD, could be potent therapeutic agents for breast cancer, blocking tumor cell proliferation and inducing apoptosis through suppression of STAT3 activity.